2005
DOI: 10.1086/428620
|View full text |Cite
|
Sign up to set email alerts
|

It Is Time to Implement Routine, Not Risk‐Based, HIV Testing

Abstract: Approximately one-quarter of a million persons in the United States who are infected with human immunodeficiency virus (HIV) do not know it. To decrease the number of such persons, primary care providers should make HIV testing a routine component of health care. HIV testing should also be offered routinely in other settings, such as emergency departments, jails, and substance abuse treatment centers. Currently, the Centers for Disease Control and Prevention and the Infectious Diseases Society of America recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 20 publications
1
45
3
Order By: Relevance
“…31 This is why the Morlat report 32 invited GPs to initiate a proposal for HIV testing that focuses on the simple message of paying attention to the classic clinical situations and monitor the opportunities for broad screening in people not recently tested as and when the opportunity arises. Routine testing could dispense with the ineffective results from referral-based risk testing 33 and would reduce stigma and discrimination. 34 The question of cost-effectiveness of HIV mass screening is still highly debated.…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…31 This is why the Morlat report 32 invited GPs to initiate a proposal for HIV testing that focuses on the simple message of paying attention to the classic clinical situations and monitor the opportunities for broad screening in people not recently tested as and when the opportunity arises. Routine testing could dispense with the ineffective results from referral-based risk testing 33 and would reduce stigma and discrimination. 34 The question of cost-effectiveness of HIV mass screening is still highly debated.…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…A study done in Botswana and Zambia found that stigma against HIV-positive persons and fear of discrimination were the key reasons for the low uptake of voluntary counselling and testing to prevent mother-to-child transmission of the virus. 21 It has been argued that routinely testing for HIV as part of health delivery would normalize testing 22 and make AIDS less stigmatized. However, it is hard to imagine how this will happen given the issues of confidentiality surrounding HIV testing and the low rate of disclosure by those testing positive.…”
Section: Stigma and Discriminationmentioning
confidence: 99%
“…1 Many of these individuals are diagnosed very late, often after developing serious AIDS-defining illnesses. 2 From an individual perspective, patients who present at an advanced stage of immune deficiency are at high risk of clinical disease and death, 3 as well as being more likely to achieve a poorer response when they receive antiretroviral therapy.…”
Section: Introductionmentioning
confidence: 99%